(untitled) (Revista científica Olimpia, 2025)
The present study aims to analyze the impact of mastectomy on the psychosocial sphere of women with breast cancer. For the development of the research, a bibliographic search was carried out in the Scielo and Google Scholar databases; during the year 2023, based on scientific articles on the impact of mastectomy on self-esteem, image impoverishment and sexuality in women with breast cancer. The search was based on inclusion and exclusion criteria. From the scientific review, 6 articles were included in the study, of which 2 were carried out in the African continent and 4 in Latin America. The results showed that women submitted to mastectomy are affected in the motivational area, feel less sexual satisfaction and present impoverishment of the body image, due to the meaning of femininity of the breast for women, so difficulties are evidenced at the time of acceptance and reincorporation of these women to daily life in society.